Editorial for economic impact of an enhanced recovery pathway for lung resection - Kumar, Rajat; Donahue, James M. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Initiatives to standardize patient care have evolved from fast tracking efforts aimed primarily at reducing costs to more sophisticated enhanced recovery after surgery (ERAS) or enhanced recovery pathways (ERPs). The goals of ERAS pathways are to minimize the perioperative stress response, reduce complications, decrease postoperative length of stay, and enable a faster return to preoperative functional status. Patient care pathways designed to achieve these goals were initially developed in colorectal surgery, and have been validated in studies and in practice (1).